Raspberry pi Based Automatic Engine Locking System for Drunken Drivers (International Journal of Innovative Technology and Exploring Engineering (IJITEE), 2023)
The prevalence of drunken driving incidents has led to numerous accidents and fatalities worldwide. To address this critical issue, this research paper presents a Raspberry Pi-based automatic engine locking system designed to prevent intoxicated individuals from operating motor vehicles. The proposed system integrates various sensors, including alcohol sensors, ignition sensors, and a Raspberry Pi microcontroller, to detect alcohol levels in the driver’s breath and disable the engine if the alcohol concentration exceeds the permissible limit. This paper discusses the system architecture, sensor integration, software implementation, and experimental results, highlighting the effectiveness and potential of the Raspberry Pi- based engine locking system in reducing drunken driving incidents.